Analisis Dampak Sosial Boikot Produk Pro-Israel - Ibtisamah Laila; Mira Mariani; Rakhmah Fakhriani; Rinjania Rinjania (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The prolonged conflict between Israel and Palestine has caused suffering on both sides, even extending to the global level. As a humanitarian response, various countries including Indonesia have boycotted products affiliated with Israel. The boycott movement is a form of protest carried out collectively by the community to oppose certain actions, products, or policies that are considered detrimental. This research uses a normative juridical approach, by analyzing regulations such as MUI Fatwa No. 83 of 2023. The results show that the boycott of pro-Israel products has a significant social impact. Positively, it encourages the growth of local products and provides moral support for Palestine. However, there are negative impacts, such as a potential increase in unemployment due to a decrease in the activities of companies affiliated with Israel. The boycott movement also serves as humanitarian solidarity and a symbol of resistance to occupation, although it needs management to reduce the negative impact on domestic labor. The public is urged to support the boycott strategically with an eye on national employment. This step is part of the global struggle for Palestinian justice and independence.